SINDROM METABOLIK PERAWAT SHIFT DAN PERAWAT REGULAR DI RSUP DR. SARDJITO TAHUN 2010 - , DR. WINDARWATI, SP.PK (K), Prof. Dr. dr. Budi Mulyono, Sp.PK(K)., MM. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The prevalence of metabolic syndrome (MS) and its components are increasing in shift workers. Based on their work characteristics, majority of nurses working in Dr. Sardjito General Hospital can be considered as shift workers. Therefore, it is important to take preventive action to prevent metabolic syndrome among them. Up until recently, metabolic syndrome and insulin resistance (IR) has not been a concern of the doctors that perform periodic health examinations for Dr. Sardjito General Hospital employees. This study aimed to determine prevalence ratio shift work with the IR and MS among nurses at Dr. Sardjito General Hospital. This was a cross-sectional study comprising of 112 subjects consisted of 48 shift nurses and 64 regular nurses. All subjects are Javanese. The study took place in September-December 2010. Statistical tests were implemeted to reveal clinical and laboratory differences between shift and regular nurses. Further analyses were conducted to establish prevalence ratios of RI and SM among them. Results showed the prevalence ratio (PR) for the occurrence of RI and SM on shift work group was 0.16 and 0.64 respectively. There are limitations in this study namely a low number of subjects, significant age differences between groups, and previous history of shift work among regular nurses.